2021
DOI: 10.1177/20480040211031068
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort study of statin prescribing for primary prevention among people living with HIV

Abstract: Objective To compare statin prescribing rates between intermediate-risk people living with human immunodeficiency virus (HIV; PLWH) and intermediate-risk patients without a diagnosis of HIV for primary prevention of atherosclerotic cardiovascular disease (ASCVD). Methods Retrospective cohort study . Electronic health record data were used to identify a cohort of PLWH aged 40–75 years with a calculated 10-year ASCVD risk between 7.5%-19.9% as determined by the Pooled Cohort Equation (PCE). A matched cohort of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The authors reported 2.5% (95% CL: −12%, 17%) higher absolute prevalence of statin prescription among PLWH. ( Nardolillo et al, 2021 ) This study addresses a different question from our study but provides insight into potential differences in statin prescription by HIV status after guideline change.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The authors reported 2.5% (95% CL: −12%, 17%) higher absolute prevalence of statin prescription among PLWH. ( Nardolillo et al, 2021 ) This study addresses a different question from our study but provides insight into potential differences in statin prescription by HIV status after guideline change.…”
Section: Discussionmentioning
confidence: 85%
“…We expanded our search to the general population and identified one study ( Tunoa et al, 2020 ) that evaluated the effect of the 2018 ACC/AHA guidelines on lipid monitoring but not statin prescription. We also identified one study ( Nardolillo et al, 2021 ) that compared statin prescriptions between PLWH and a matched cohort of people without HIV after the 2018 guideline change in a safety-net health system. The authors reported 2.5% (95% CL: −12%, 17%) higher absolute prevalence of statin prescription among PLWH.…”
Section: Discussionmentioning
confidence: 99%